SOUTH AFRICA AND THE SADC STAND-BY FORCE - Mandrup, Thomas (Scientia Militaria - South African Journal of Military Studies, 2011)
The regional powerhouse, South Africa, has since the introduction of the nonracial democratic dispensation in 1994, played a central and important role in the formation of both the regional and continental security architecture. With the establishment of the Southern African Development Community (SADC) in 1992, one of the central areas of collaboration for the community was envisioned to be security, understood within a broadened human security framework. Security was therefore from the outset one of the cornerstones of integration in the SADC. It was believed that the formation of a security community would help dismantle the enmities that had plagued regional relations during the apartheid era. For some parties, institutionalisation of relations pointed to a means of stabilising and disseminating a particular order. Such institutions depict the power relations prevailing at the time of their establishment, which, however, can change over time (Cox 1981:136). The integration ambition surrounding security correlated with the ambitions of South Africa, the new democratic government in the regional powerhouse. South Africa and its overall foreign policy ambitions desired the pursuit of peace, democracy and stability for economic growth and development in the region and within South Africa itself.